STRATEGI PENINGKATAN DAYA SAING UMKM BINAAN PT. PERTAMINA HULU ROKAN KECAMATAN MANDAU MELALUI ANALISIS SWOT - Nazrantika Sunarto; Dwi Astuti; Muhammad Arif, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
PHR focuses its program on developing MSMEs to adapt to the digital economy. PT. PHR focuses on efforts to help MSMEs move from traditional marketing to digital marketing in order to increase competitiveness. This study aims to determine the internal factors and external factors in determining the competitiveness of SMEs assisted by PT. PHR Mandau District, To determine the right strategy in order to maximize the strength factors possessed and minimize the weakness factors possessed by MSMEs fostered by PT. PHR Mandau District. The data was carried out by survey, observation, and deph interview to MSME business actors assisted by Pertamina Hulu Rokan, Mandau District. Data analysis using SWOT analysis The results of research based on internal and external factors are the most appropriate strategy used by MSME PT. PHR so that it can become the main choice of consumers in increasing competitiveness is to expand the marketing network and keep records of business finances properly.